2017
DOI: 10.1017/s2045796017000038
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation and behaviour among community and health care seeking populations in five low- and middle-income countries: a cross-sectional study

Abstract: The high prevalence of suicidal ideation in primary care points towards important opportunities to implement suicide risk reduction initiatives. Evidence-supported strategies including screening and treatment of depression in primary care can be implemented through the World Health Organization's mental health Global Action Programme suicide prevention and depression treatment guidelines. Suicidal ideation and behaviours in the community sample will require detection strategies to identify at risks persons not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
107
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 39 publications
(52 reference statements)
18
107
2
Order By: Relevance
“…In fact, only 23% mentioned that their loved one had shared their suicide ideation. In many other low-income settings, suicide ideation disclosure is rare, often due to fear and stigma (Hagaman, et al, 2013; Jordans, et al, 2017). Determining opportunities and appropriate strategies to encourage disclosure will be important for community prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, only 23% mentioned that their loved one had shared their suicide ideation. In many other low-income settings, suicide ideation disclosure is rare, often due to fear and stigma (Hagaman, et al, 2013; Jordans, et al, 2017). Determining opportunities and appropriate strategies to encourage disclosure will be important for community prevention.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings are limited to women or to clinical-care settings so that little is known about male suicides as well as those that fail to emerge in the health system. Additionally, a recent five-country study found that Nepal community and clinical populations had high rates of suicide ideation, but the lowest amounts of ideation disclosure and help-seeking following an attempt (Jordans, et al, 2017). This underscores the importance of further research on why suicidal thoughts are not disclosed, as well as a better understanding of perceived drivers and meanings of suicidal deaths in Nepal (Jordans, et al, 2017; Jordans, et al, 2014; Pyakurel, et al, 2015; Marahatta, et al, 2016; Pradhan, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Nepal, a recent study found suicide disclosure to family/friends and help-seeking to be very low, suggesting that active clinical screening maybe a useful strategy for prevention (69). Compared to depression, a more sensitive marker of risk in Nepal may include having a family member or close friend that recently engaged in suicidal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It affects all people in all age groups worldwide(4). Depression has high impact at the individuals',family members', and at the country level (2,5,6). At the individual level, depression causes social and occupational functioning impairment (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Informal help usually offered by friends, family, religious leaders (priests), or other non-health professionals. Individuals in the community have been found higher support from informal help providers than formal help providers (5,39). It is more di cult and a challenge to explore informal help as informal help occurs frequently and studies are limited (40).…”
Section: Introductionmentioning
confidence: 99%